Variety in the Typography of Yiddish: 1535-1635 - Zafren, Herbert C. (Hebrew Union College annual, 1982)
Early Yiddish printing has been little studied as part of the history of printing. The unusual alphabet that was used for Yiddish for centuries has been noticed, of course, but not thoroughly examined. Prague Hebrew type of 1540 has incorrectly been called the Vorlage of the Yiddish Type which appeared as early as 1534/35. This paper offers a short summary of my theory that Yiddish Type is Ashkenazic Rabbinic Type which ceased being used for Hebrew, except in Prague, and thus became available for Yiddish. The surprising facts that Yiddish was printed in more than twenty cities in its first century and that more than twenty different typefaces were cut for Yiddish alone are documented. Facsimiles of these typefaces allow comparison of the many faces for the first time, and a table of the typefaces highlights the spread of Yiddish printing activity and the wandering of the typefaces themselves. Finally, the paper accounts for the use of type other than Yiddish Type for Yiddish and the very occasional use of Yiddish Type for Hebrew.